2015
DOI: 10.1002/wdev.169
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control of midbrain dopaminergic neuron development

Abstract: The authors have declared no conflicts of interest for this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
91
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(92 citation statements)
references
References 123 publications
1
91
0
Order By: Relevance
“…Recently, much work has focused on the progenitor zone that gives rise to dopamine (DA) neurons in the midbrain, with a goal of deriving DA neurons from stem cells, for modeling and ultimately treating Parkinson's disease (Arenas et al, 2015;Blaess and Ang, 2015;Smidt and Burbach, 2007;Smits et al, 2006;Studer, 2012). In the developing CNS, DA neurons arise from the mesodiencephalic floor plate (mdFP), here defined by the co-expression of Shh, Foxa2 and Lmx1a rostral to the midbrain-hindbrain boundary (MHB), due to the concerted action of Shh, Fgf and Wnt signaling pathways (Arenas et al, 2015;Blaess and Ang, 2015;Joksimovic and Awatramani, 2014;Lahti et al, 2012;Luo and Huang, 2016;Smits et al, 2006;Wurst and Prakash, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, much work has focused on the progenitor zone that gives rise to dopamine (DA) neurons in the midbrain, with a goal of deriving DA neurons from stem cells, for modeling and ultimately treating Parkinson's disease (Arenas et al, 2015;Blaess and Ang, 2015;Smidt and Burbach, 2007;Smits et al, 2006;Studer, 2012). In the developing CNS, DA neurons arise from the mesodiencephalic floor plate (mdFP), here defined by the co-expression of Shh, Foxa2 and Lmx1a rostral to the midbrain-hindbrain boundary (MHB), due to the concerted action of Shh, Fgf and Wnt signaling pathways (Arenas et al, 2015;Blaess and Ang, 2015;Joksimovic and Awatramani, 2014;Lahti et al, 2012;Luo and Huang, 2016;Smits et al, 2006;Wurst and Prakash, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In the developing CNS, DA neurons arise from the mesodiencephalic floor plate (mdFP), here defined by the co-expression of Shh, Foxa2 and Lmx1a rostral to the midbrain-hindbrain boundary (MHB), due to the concerted action of Shh, Fgf and Wnt signaling pathways (Arenas et al, 2015;Blaess and Ang, 2015;Joksimovic and Awatramani, 2014;Lahti et al, 2012;Luo and Huang, 2016;Smits et al, 2006;Wurst and Prakash, 2014). In terms of boundaries delimiting the DA progenitor zone, several studies have demonstrated that the caudal limit of DA neuron production is at the MHB defined by the caudal limit of Otx2 expression (Brodski et al, 2003;Joyner et al, 2000;Simeone et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to generate mdDA neurons Wnt/β-catenin signaling has to suppress expression of Shh in this region (Joksimovic et al, 2009;Joksimovic and Awatramani, 2014;Wurst and Prakash, 2014). Wnt1/β-catenin signaling also sequentially induces the expression of several transcription factors (TFs) in postmitotic mdDA precursors, such as Lmx1a and Pitx3, both of which are necessary for proper mdDA neuron development (Blaess and Ang, 2015;Hegarty et al, 2013;Veenvliet and Smidt, 2014;Wurst and Prakash, 2014). Pitx3 regulates the transcription of several genes necessary to ensure the correct differentiation, function and survival of the substantia nigra pars compacta (SNc) mdDA neurons (Jacobs et al, 2009(Jacobs et al, , 2007Luk et al, 2013;Maxwell et al, 2005;Peng et al, 2011;Veenvliet et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Pitx3 in this area has been found to cooperate with the nuclear receptor Nr4a2 (also known as Nurr1) and with Aldh1a1 (also known as Raldh1 and Ahd2) (Jacobs et al, 2009(Jacobs et al, , 2007. Further genes implicated in mouse mdDA neuron development include the TFs Lmx1b, Engrailed (En1/2), and Neurog2 (also known as Ngn2) (Blaess and Ang, 2015;Hegarty et al, 2013;Veenvliet and Smidt, 2014).…”
Section: Introductionmentioning
confidence: 99%